Adhering maternal platelets can contribute to the cytokine and chemokine cocktail released by human first trimester villous placenta. Issue 11 (November 2015) - Blaschitz, A.; Siwetz, M.; Schlenke, P.; Gauster, M.
Abstract: Placental villous explant culture has been increasingly recognized as suitable model to study secretion of inflammatory and immune modulating factors by human placenta. Most of these factors likely derive from the syncytiotrophoblast, whereas extraplacental sources such as maternal peripheral blood cells are rarely considered. Due to their small size and absence of a nucleus, platelets adhering to perivillous fibrinoid of normal placenta are frequently ignored in routine immunohistochemistry. Here we demonstrate adhering maternal platelets on first trimester placental villi after explant culture and point out that platelet-derived factors must be considered when analyzing the inflammatory secretion profile of human placenta. Highlights: Maternal platelets can be detected on first trimester placental explants. They adhere to perivillous fibrin-type fibrinoid. Platelet-derived factors, such as CCL5 and CXCL4 are released into culture supernatants. Platelet-derived factors can distort analysis of the placental secretion profile.